Evaluation of the Cavite City Library and Museum - Mojica, Michael Anthony A.; Gonzales, Grace Marie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
The purpose and objectives of the public library are described in relation to three basic concerns - the needs of the people who use the libraries, the need to ensure that the library is located in a suitable site, and the need for effective means for operating it and developing its services (Mahapatra and Thomas 1996). The Cavite City Library and Museum was established by the city government to serve as an information and learning center. An evaluation of this library would greatly promote its development according to the Minimum Standards for Public Libraries and to the functions and objectives of a public library. The objective of this study is to find out the nature of the collection of the library, to ascertain if the library meets the information needs of its clients, to find out if the library meets the Minimum Standards for Public Libraries set by the PLAI, to identify the areas where the library fails to meet the standards, to know the strengths and weaknesses of the library.
The descriptive survey method was used in gathering data on how users perceive the library collection and services. A questionnaire was also prepared for the head librarian to collect more data about the collection and services of the library. Out of 79 respondents, 61 (77 percent) are females and 18 (23 percent) are males. All of them are students, 54 (68 percent) are in High School, 15 (19 percent) are in the Elementary level and 10 (13 percent) are in College. Results of the survey show that 53 (67 percent) of the respondents are satisfied with the collection while 44 (56 percent) rated the services offered by the library as adequate.
Despite lacking some of the minor recommendations of the Minimum Standards for Public Libraries, it is still fulfilling its functions of a public library and therefore meets the standards.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Cavite City Library and Museum; Public libraries -- Evaluation. -- Philippines -- Cavite City